2022
DOI: 10.21203/rs.3.rs-2049362/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What motivated men to start PrEP? A cross-section of men starting PrEP in Buffalo City Municipality, South Africa

Abstract: Background Compared to women, South African men are less likely to know their HIV status (78% vs 89%), have suppressed viral loads (82% vs 90%), or access HIV prevention services. To achieve epidemic control where heterosexual sexual behavior drives transmission, interventions to improve the uptake of HIV testing services (HTS) and prevention services must also target cis-gendered, heterosexual men. There is limited understanding of these men’s needs and wants with regards to accessing pre-exposure prophylaxi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
2
3
0
1
Order By: Relevance
“…Previous studies have found that negative provider attitudes, lack of privacy, long waiting times and HIV testing are substantial barriers to PrEP uptake and use [12, 22]. In our study, we found several health system factors which supported PrEP use and uptake.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Previous studies have found that negative provider attitudes, lack of privacy, long waiting times and HIV testing are substantial barriers to PrEP uptake and use [12, 22]. In our study, we found several health system factors which supported PrEP use and uptake.…”
Section: Discussionsupporting
confidence: 52%
“…However, we did not explore the potential impact of alcohol consumption on consistent PrEP use and retention in PrEP care, an area that may be explored in future studies. Previous studies have found that negative provider attitudes, lack of privacy, long waiting times and HIV testing are substantial barriers to PrEP uptake and use [12,22]. In our study, we found several health system factors which supported PrEP use and uptake.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Adicionalmente, um estudo realizado na África do Sul (Smith et al, 2023), sugeriu que homens cisgênero heterossexuais possuem uma menor adesão à PrEP devido a vários fatores sociais, os quais são destaque: o desconhecimento de que a profilaxia é para toda a população que tenha interesse em se proteger ou que tenha comportamentos de risco -incluindo para homens heterossexuais; o medo de fazer a testagem para HIV, a qual é um pré-requisito para dar início ao tratamento; e, por fim, o acesso a serviços de saúde convencionais para realização deste tipo de prevenção. Além disso, notou-se que o grupo de homens heterossexuais não demonstrou estigma em relação ao uso da PrEP, nem em relação aos usuários da profilaxia, reagindo positivamente aos que fazem uso, pois estes pacientes possuem uma maior responsabilidade com a própria saúde.…”
Section: Discussionunclassified